Efficacy of local injection therapy with hyaluronic acid of different molecular weight in patients with knee osteoarthritis - V. E. Bialik; E. I. Bialik; M. A. Makarov; S. A. Makarov; V. A. Nesterenko (Научно-практическая ревматология, 2019)
Intra-articular administration of hyaluronic acid (HA) is one of the methods of conservative treatment of knee osteoarthritis (OA). However, the data of its efficacy in the modern literature are contradictory.Objective: to assess the efficacy of intra-articular administration of HA preparations with different molecular weight in the treatment of patients with knee OA and to study the factors that can influence the effectiveness of such therapy.Subjects and methods. HA preparations were administered to 60 patients with idiopathic and posttraumatic knee OA. The ratio of women to men was 3:1. The average age was 59.5±13.7 years and body mass index – 30.3±5.8 kg/m2. The presence of enthesitis was evaluated prior to treatment by the characteristic clinical picture. The x-ray stage of OA was determined in accordance with the classification of Kellgren–Lawrence. Distribution of of knee joint lesions, relationship of femur and tibia anatomical axes, presence of varus and valgus deformities were also evaluated. The patients were divided into three groups: 18 patients received low-molecular (LM), 19 – medium-molecular (MM) and 23 – high-molecular (HM) HA. To assess the efficacy of the treatment the severity of pain on a visual analog scale (VAS) and the total score of the Knee injury and Osteoarthritis Outcome Score (KOOS) questionnaire before, 1, 3 and 6 months after treatment were evaluated.Results and discussion. Enthesitis was detected in 17 (28,3%) patients. Stage I of knee OA was diagnosed in 10 (16.6%), II – in 36 (60%) and III – in 14 (23.3%) patients. Varus deformity was detected in 43 (71.7%) patients, neutral axis of the lower limb - in 14 (23.3%), valgus deformity – in 3 (5%). The most significant decrease in the severity of pain was noted in patients with stage I of knee OA: from 54±17.1 to 10.0±10.0 mm. At stage II, the pain decreased from 59.4±12.6 to 45.5±20.3 mm, and at stage III – from 66.4±13.5 to 60.7±23.3 mm. By the 6th month, the severity of pain in patients with enthesitis was higher, and the values of KOOS total score were worse than in patients without it. At stages II and III of knee OA, the ratio of positive to unsatisfactory results for MM, LM and HM HA was as follows: 2:1, 3:1 and 3.6:1. In the group of patients with excellent results, the value of varus deformation averaged 8.5±1.5°, in patients with a good result – 9.8±2.8°, with a satisfactory result – 11.3±4.5°, and with an unsatisfactory – 11.5±3.2°.Conclusion. Intra-articular injection of HA is very effective at stage I of knee OA. The expression and duration of this effect are reducedwith decrease of cartilage thickness and increase of knee joint varus deformation (i.e., at the II and III stages of knee OA). The presence of varus deformation does not affect HA efficacy. Three factors are important: the appearance of varus deformation of the lower limb with initially neutral axis; the increase of varus deformation; the value of varus deformation >10°.